2010
DOI: 10.1007/s10549-010-1264-6
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of metastatic tissue from patients with bone metastases from breast cancer

Abstract: Biopsies of metastatic tissue are increasingly being performed. Bone is the most frequent site of metastasis in breast cancer patients, but bone remains technically challenging to biopsy. Difficulties with both tissue acquisition and techniques for analysis of hormone receptor status are well described. Bone biopsies can be carried out by either by standard posterior iliac crest bone marrow trephine/aspiration or CT-guided biopsy of a radiologically evident bone metastasis. The differential yield of these tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 16 publications
2
37
1
Order By: Relevance
“…Tumour heterogeneity may be attributable to tumour biological drift, selective pressure of therapy leading to clonal selection with the development of a novel tumour cell clone, or the presence of small sub-clones routinely undetected within the primary tumour. Along this line, as prospectively reported by Hilton and colleagues [45] tumour and metastatic deposits occurred, and a full concordance among metastases arising in multiple bone sites, suggesting the occurrence of a metastasising clone diverging in terms of ER immunoreactivity from the primary tumour. Whether and how ER, PgR and HER2 conversion modifies the treatment schedule and affects breast cancer patients survival has not been fully elucidated, and the available data are scarce and conflicting, as well as the optimal time to retest tumour biology.…”
Section: Discussionsupporting
confidence: 78%
“…Tumour heterogeneity may be attributable to tumour biological drift, selective pressure of therapy leading to clonal selection with the development of a novel tumour cell clone, or the presence of small sub-clones routinely undetected within the primary tumour. Along this line, as prospectively reported by Hilton and colleagues [45] tumour and metastatic deposits occurred, and a full concordance among metastases arising in multiple bone sites, suggesting the occurrence of a metastasising clone diverging in terms of ER immunoreactivity from the primary tumour. Whether and how ER, PgR and HER2 conversion modifies the treatment schedule and affects breast cancer patients survival has not been fully elucidated, and the available data are scarce and conflicting, as well as the optimal time to retest tumour biology.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, we report here for the first time a statistically significant correlation between previous systemic treatments and modifications in receptors' expression. Several studies have addressed the issue of concordance/ discordance in receptors expression between primary tumor and metastases [9,[12][13][14][15][16][17][18][19][20][21][22][23][24]. Published studies have found discordance rates for ER status ranging from 10.2% to 56%, PR status ranging from 24.8% to 48.6%, and HER2 status ranging from 2.9% to 16%.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable proportion of patients with relapsed tumors had changes in ER, HER2 or TOP2A status. Biopsy confirmation is associated with a number of logistic as well as technical challenges, especially in the case of bone metastases [28]. However, it has become standard practise in our institution.…”
Section: Discussionmentioning
confidence: 99%